Uptake, accumulation, and metabolism of 14C-linuron - Voll, Elemar; Filho, Ricardo Victória; Corbin, Frederick T.; Worsham, Arch D. (Pesquisa Agropecuaria Brasileira, 2014)
In order to get information on physiological process of weed control of linuron in mixture with alachlor experiments with soybeans (Glycine max (L.) Merr. cv. Ramson) and cucumber (Cucumis sativus L. cv. Wisconsin SMR58 Pickles) were carried out in pots filled with soil and in nutrient solution. The 14C-linuron sample presented a specific activity of 6.84 uCi/mg. In pots filled with soil, alachlor protected cucumber seedlings, but not soybeans and lambsquarter from linuron phytotoxicity, when both were incorporated at planting time. In nutrient solution with alachlor and linuron, three days old soybean and cucumber seedlings did not show alachlor protection against linuron damage, adding  phytotoxicity effects of both. Linuron absorption and metabolism was greater in soybeans than in cucumber. Higher linuron content was observed in the unifoliolate leaves of soybeans and in the cotyledons of cucumber. Linuron reduced soybeans and cucumber biomass, but cotyledons and hypocotyl of soybeans were not affected. Linuron alone reduced water absorption in soybeans and cucumber; this reduction was enhanced when in mixture with alachlor.
Keywords: Glycine max; soybeans; cucumber; phytotoxicity; metabolism